Respiratory support in severe traumatic brain injury (literature review) - D.A. Krishtafor; O.M. Klygunenko; O.V. Kravets; V.V. Yekhalov; A.A. Krishtafor (Medičnì Perspektivi)
Patients with traumatic brain injury (TBI) are the largest group of victims at the emergency departments. Up to 20% of patients with severe TBI require endotracheal intubation and prolonged mechanical ventilation. The ventilation parameters choice should be focused on the normal arterial blood gas composition. Hypoxia causes secondary damage to the brain tissue, and hyperoxia carries risks of oxygen toxicity. Hypercapnia leads to cerebral vasodilatation, increased intracranial pressure (ICP) and the risk of cerebral edema. Hypocapnia promotes cerebral vasoconstriction, which reduces cerebral blood flow and ICP, but also leads to cerebral tissue ischemia, so prolonged hyperventilation in TBI is not currently recommended. Patients with TBI often require sedation to synchronize with the respirator. The drugs of choice are propofol and midazolam. Routine use of muscle relaxants is not recommended. The initial ventilation mode should provide a certain respiration rate to achieve normocapnia, while allowing the patient to make breathing attempts. Support ventilation modes are used while weaning from mechanical ventilation. Promising in predicting extubation success is the assessment of the VISAGE score, which includes visual pursuit, swallowing, age, and the Glasgow coma score. Modern principles of respiratory support in severe TBI include: tracheal intubation by Glasgow coma score ≤8 ; early mechanical ventilation; PaO2 80-120 mm Hg (SaO2 ≥95%); PaCO2 35-45 mm Hg; tidal volume ≤8 ml/kg; respiratory rate ≈20/min; PEEP ≥5 cm H2O; head elevation by 30°; sedation in poor synchronization with the respirator; weaning through support ventilation modes; extubation when reaching 3 points on the VISAGE scale; early (up to 4 days) tracheotomy in predicted extubation failure.